(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Obstetric comorbidities significantly increase the risk of adverse obstetric outcomes because of their association with complications that can occur suddenly and escalate rapidly. Case presentation: A morbidly obese 26-year-old primigravida initially presented with first-trimester bleeding. She consistently declined monitoring and was not adherent to the multidisciplinary treatment plans despite serial counseling. This state persisted even when she was diagnosed with gestational diabetes mellitus and preeclampsia. She incurred gross fetal macrosomia and was admitted at term for induction of labor. By the third prostaglandin, there was overt fetal tachycardia that necessitated an emergency cesarean delivery. Failed spinal anesthesia necessitated generalization. Access was impeded by a massive panniculus, necessitating tape retraction to reveal the surgical site. A distressed apneic baby was delivered, after which she developed an atonic uterus that necessitated uterine brace suturing and intramyometrial PGF2α. The baby underwent therapeutic hypothermia. Postoperatively, she was monitored and underwent repeated counseling. Discussion: This patient was noncompliant to medication and monitoring, she had multiple interacting comorbidities, and she ended up having an avoidable multiple near-miss. There is a need to develop an obstetric comorbidity scoring index and validate it locally. Conclusion: If guided by a logical algorithmic sequence of guided responses, the development and application of a local risk and comorbidity scoring index may substantively reduce the risk of adverse obstetric outcomes. This is vital if sustainable development goals are to be realized.